Sex and size affect annual survival in a threatened sand lizard - Kacoliris, Federico Pablo (2013)
The sand-dune lizard Liolaemus multimaculatus is a threatened species endemic to the coastal ecosystems of Argentina. We assessed annual survival in one of largest known populations, using a mark recapture approach to estimate survival rates between 2006 and 2008. We found effects of size class, sex and year on survival rates. Average survival was 0.474 in adult males, 0.672 in adult females, 0.415 in juvenile males and 0.470 in juvenile females. The observed differences could be related to higher predation of juvenile and male lizards.